THE IMPACT OF EMOTIONAL STRESS ON COGNITIVE FUNCTIONING IN UNIVERSITY STUDENTS: A PATHOPSYCHOLOGICAL ANALYSIS - Tajiboyeva Odinakhon Ruatamjon qizi,Muydinova Oisha Mirzarakhmatovna (International Journal of Literature and Language Studies, 2026)
Emotional stress among university students is a growing psycho-educational and clinical concern that significantly affects cognitive functioning. This article presents a pathopsychological analysis of the relationship between emotional stress and cognitive processes, particularly attention, memory, thinking, and information processing. The study is based on a structured review of contemporary scientific literature and integrates evidence from clinical psychology, neurophysiology, and educational medicine. Special emphasis is placed on the role of chronic psychoemotional tension in the disorganization of higher mental functions. The findings indicate that prolonged emotional stress leads to functional destabilization of cognitive processes through dysregulation of emotional-volitional control, reduced mental efficiency, and increased psychological fatigue. The article also discusses evidence-based psychological and behavioral strategies for reducing stress and improving cognitive performance in students.